Identifying genes associated with biofilm production in Pseudomonas aeruginosa - Chee, Jessica (The Meducator, 2018)
Pseudomonas aeruginosa is an opportunistic pathogen associated with a variety of life-threatening diseases. Infections caused by P. aeruginosa can be nearly untreatable because of its multidrug-resistance. One of the characteristics of P. aeruginosa that helps it survive in high drug concentrations is its ability to form biofilms–large communities of cells encompassed by extracellular polymeric substances that defend against many antibiotics. In fact, sub-minimum inhibitory concentrations of antibiotics stimulate biofilm production. This project aims to identify genes associated with biofilm induction in P. aeruginosa by screening a transposon mutant library for mutants that fail to show increased biofilm production when exposed to sub-minimum inhibitory concentrations of cefixime, tobramycin, and thiostrepton. So far, we have identified one gene, PA2714, that encodes a predicted molybdopterin oxidoreductase required for biofilm production. Because of the strong association between biofilm production and antibiotic tolerance in P. aeruginosa, the gene identified in this screen may be a useful therapeutic target for novel antimicrobials that can disrupt biofilm formation.